(untitled) - Everitt, William Littell (New York, 1956)
Chapter 1. Fundamental principles of communication networks, Chapter 2. Methods of network - behavior analysis, Chapter 3. Steady - state analysis and network theorems, Chapter 4. Resonance,...
Keywords: Telecommunication,Viễn thông